Maternal Mortality: Sharing Experience from Banke District - Sushma Acharya; S Acharya (Journal of Lumbini Medical College, 2013)
Maternal mortality is a global burden, with more than 500,000 women during each year due to pregnancy and childbirth related complications¹. Globally, 60-80% of maternal deaths are due to obstetric complications, these are haemorrhage, sepsis (infection), obstructed labour and hypertensive disorder of pregnancy and complications of unsafe abortion.² OBJECTIVE: To identify the causes of maternal mortality. MATERIALS AND METHODS: The study was conducted in Banke district. Descriptive cross-sectional study was adopted, during a period of one year from July 2011 to June 2012 at Banke District in Western Region of Nepal. Non probability purposive sampling method was used for collecting the data. Both primary and secondary sources of data were taken for the study. RESULTS: The maximum number of maternal deaths was from Madheshi and Muslim community, most of them were illiterate. The main cause of maternal deaths was post partum haemorrhage. CONCLUSION: Nepal achieved an impressive reduction in maternal mortality between 2001 and 2006, but maternal deaths remain high. The trends of death from snake bite, suicide, epilepsy and physical assault are the new causes.